Supervisi Pendidikan Islam (Supervision of Islamic Education) - depri, deprizon (JURNAL ISLAMIKA, 2021)
Abstract: Educational institutions in Indonesia are sheltered and controlled by two ministries where public schools are controlled by the Ministry of Education and Culture while religious schools, in this case madrasas are controlled by the Ministry of Religion. However, this educational institution will always receive supervision where the public school supervisors are from the Ministry of Education and Culture except for the PAI teacher and the Madrasah supervisor from the Ministry of Religion. The effective functioning of an educational institution, be it public education or religious education or Madrasa can not be separated from the active role of a supervisor, because in fact the supervisor will always control the course of education in the school or madrasa institution carefully. All forms of oversight carried out aim that an education that takes place in educational institutions runs according to the direction and objectives of the education curriculum both locally and nationally. All supervision activities carried out by a school supervisor are expected to all lead to improving the quality of the school and education in general, and specifically supervision aimed at improving the quality of the school. Keywords: Supervision, Islamic Education, Coaching and Guiding.